1998
DOI: 10.1002/pro.5560071122
|View full text |Cite
|
Sign up to set email alerts
|

The orientation and dynamics of substance P in lipid environments

Abstract: The membrane-associated conformation of substance P (RPKPQQFFGLM-NH2) has been previously proposed to be the NKI-receptor-active conformation. In this work, NMR methods are applied to explore the orientation and dynamics of substance P at lipid surfaces for which the peptide's three-dimensional structure had been previously determined. Here the presence of dodecylphosphocholine (DPC) or sodium dodecylsulfate (SDS) micelles has been found to cause sequence specific changes in the acid-and base-catalyzed amide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The conserved C-terminal hydrophobic residues (Table 1) are localized on the same side of the peptide as has been observed in the DPC-bound peptide [56]. Neutron diffraction and amide-exchange experiments have been carried out to investigate the interactions of SP and NKA with the micelles or phospholipids bilayers [179][180][181]. Amide-exchange experiments in SDS micelles suggest interactions of Phe8, Phe9 and Gly10 residues in the interfacial region of the lipid micelle headgroups [179].…”
Section: Substance P (Sp)mentioning
confidence: 94%
See 1 more Smart Citation
“…The conserved C-terminal hydrophobic residues (Table 1) are localized on the same side of the peptide as has been observed in the DPC-bound peptide [56]. Neutron diffraction and amide-exchange experiments have been carried out to investigate the interactions of SP and NKA with the micelles or phospholipids bilayers [179][180][181]. Amide-exchange experiments in SDS micelles suggest interactions of Phe8, Phe9 and Gly10 residues in the interfacial region of the lipid micelle headgroups [179].…”
Section: Substance P (Sp)mentioning
confidence: 94%
“…Neutron diffraction and amide-exchange experiments have been carried out to investigate the interactions of SP and NKA with the micelles or phospholipids bilayers [179][180][181]. Amide-exchange experiments in SDS micelles suggest interactions of Phe8, Phe9 and Gly10 residues in the interfacial region of the lipid micelle headgroups [179]. Neutron diffraction experiments clearly demonstrate that SP interacts with both zwitterionic and anionic membranes and the C-terminus of the peptide is positioned at a depth below the membrane surface [180].…”
Section: Substance P (Sp)mentioning
confidence: 98%
“…3,4 The interaction of SP with lipid monolayers and bilayers has been investigated extensively in the past. [5][6][7][8][9][10][11][12][13][14] Seelig and Macdonald concluded that SP does not insert into zwitterionic palmitoyloleoylphosphatidylcholine monolayers, 5 but does insert into monolayers with negatively charged 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-glycerol monolayers. It was proposed by Schwyzer that SP interacts with its receptors through a membranemediated mechanism, 6,7 but this mechanism was disputed by Seelig et al for several SP agonists.…”
Section: Introductionmentioning
confidence: 97%
“…SP is known to form an K-helical structure in hydrophobic environments but not in aqueous solution [23], while it has a positive charge distribution over its sequence, supporting the ¢nding that SP is a PAP. Therefore, the neuropeptide SP was tested for its preference for mitochondria-like membranes.…”
Section: Discussionmentioning
confidence: 83%